Edukasi Perilaku Cuci Tangan Pakai Sabun (CTPS) Pada Lansia di Panti Sosial Tresna Werdha Teratai - Nathasa Weisdania Sihite; Podojoyo Podojoyo; M. Yusuf (Universitas Muhammadiyah Yogyakarta, 2021)
Cleanliness is an essential factor in supporting health programs in Indonesia, one of which is handwashing with soap (CTPS). The application of CTPS in everyday life in the community is able to prevent various diseases. Knowledge of CTPS among the elderly is still relatively low and is often neglected. Meanwhile, the highest number of deaths by age in Indonesia is at the age of 60 years (elderly) due to a drastic decline in the immune system in the group. Therefore, increasing knowledge of CTPS in the elderly and education in the health sector is necessary. The main objective of this community service program was to improve the attitudes, knowledge, and skills of the elderly in social institutions in maintaining health, especially on hygiene. Accordingly, this is expected to increase life expectancy for the elderly. The methods in this service program were through tutorials and mentoring practices. This community service activity was conducted for the elderly at the Tresna Werdha Teratai Social Home in Palembang. The results were reflected by the enthusiasm of the elderly participants who attended. The result showed the improved posttest score in the average knowledge of the elderly from the initial score of 54 to 71 points. Increasing the knowledge and skills of the elderly towards CTPS can be applied in everyday life, thereby reducing susceptibility to various diseases.